The Normal school : an opportunity for rural women, 1916-1925 - Bertelsen, Dana Rae (My University, 2008)
This paper focuses on the effect Normal Schools had on the rural women who attended the institutions, using Eau Claire Normal as a case study for the larger Normal School movement and women in higher education from 1916-1925. This paper examines the school and the town where the school resided, student activities, the different programs for one could enroll, student experience in the school and after graduation, and employment for the graduates. These sections explain how the rural women attending the Normal school used the institution to expand their intellectual, cultural, social, and economic abilities.
Keywords: Rural women--Wisconsin--Social conditions; Teachers colleges--Wisconsin--Eau Claire--History; Women college students--Wisconsin--History; Eau Claire State Normal School--History; Rural women--Education--Wisconsin